PENGARUH SERTIFIKASI FAIR TRADE TERHADAP KEMAJUAN SEKTOR PERTANIAN KAKAO DI GHANA (2003-2008) - Amelia Rant; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The imbalance of cocoa market had led to a disastrous impact forproducer in the lowest level, the farmers. Ghanaian cocoa farmers the majorityhave complex poverty problems. The low Cocoa prices trigger a variety of socialand economic problems. This study aims to determine the effect on the progress ofFair Trade certification of cocoa farming sector in Ghana, and role of KuapaKokoo in addressing this problem.Method applied in doing this research is description with aim to depict aphenomenon in this case writer tries explains events relating to effect ofcertificate Fair Trade on Organisation Farmer Kuapa Kokoo in overcomingunfair trading cocoa of affecting at Ghana cocoa farmer.Considering its strategy on the support for fair trade program for cocoafarmers, Kuapa Kokoo farmers' role as the company in providing security againstvarious aspects of the Ghanaian cocoa trade. Kuapa Kokoo also cooperate inother public companies in shaping their chocolate company Divine Chocolate is.Implementation of fair trade and programs to farmers by Kuapa Kokoo cocoaGhana also faced with constraints that are not small. The main obstacle faced isthe lack of support for the Kuapa Kokoo to run kaako trade in Ghana and thesmall volume of fair trade market is causing not all farmers can participate in it.Keywords: Effects of Fair Trade Certification, Kuapa Kokoo’s Role, GhanaCocoa Farmer